(UN)USED POTENTIAL – THE PROCESS OF BECOMING INDEPENDENT BY YOUNG-ADULT FOSTER CARE CHILDREN - Kędzierska, Hanna; Zagulski, Sylwester (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The transition to adulthood of young people leaving foster care is an important research topic. The results of many international studies show that care leavers are at high risk of social exclusion. In 2023, an amendment to the Act on foster care was introduced in Poland to increase the number of successful transitions into adulthood. The aim of the empirical study we undertook was to analyse the relevance of long-term care solutions implemented in Poland for children leaving foster care, from the perspective of professional caregivers of the process of becoming independent. The study had the character of a field reconnaissance (Minski, 2017), as it allowed us to verify the issues undertaken before the next stage of the research. We decided to conduct individual in-depth interviews with guardians of empowerment. Our research shows that, despite many pertinent statutory solutions, in practice the system does not work as it should.  The main problem is the systemic marginalization of carers' problems and the lack of substantive and psychological support for them.